Detection of Hanseniaspora opuntiae in anovaginal samples of pregnant women in Rio de Janeiro, Brazil—a case report - Pinto, Tatiane Nobre; Oliveira, Laura M. A.; da Costa, Gisela L.; Costa, Natália Silva; Francisco, Elaine Cristina; Pinto, Tatiana C. A.; Oliveira, Manoel M. E. (Frontiers in Cellular and Infection Microbiology, 2024)
In this study, we report the first isolation of Hanseniaspora opuntiae obtained from four pregnant women in Brazil. Clinical isolates were obtained from four samples taken between the 35-37 gestational weeks, as part of the routine antenatal care for maternal colonization screening for Streptococcus agalactiae group B. The patients were immunocompetent, with two of them diagnosed with gestational diabetes mellitus. Species identification was performed by MALDI-TOF MS and rDNA sequencing. While Hanseniaspora species have not traditionally been considered a typical opportunist pathogen, our findings emphasize the importance of investigating and screening for Hanseniaspora in pregnant populations, highlighting H. opuntiae as potential agent of human infections.